IBM eServer xSeries and BladeCenter Server management - Watts, David (IBM redbooks., 2005)
The systems management hardware that is part of IBM xSeries and BladeCenter servers serves as an important part of the overall management strategy for customers. This hardware, either integrated into the server or BladeCenter chassis, installed at the factory as an adapter, or available as an option, provides vital information back to the administrator and gives the administrator the ability to remotely control the server, even when the operating system is not running. This IBM Redbook describes the full range of management hardware currently available for the xSeries and BladeCenter systems. We cover the integrated Baseboard Management Controller , the Remote Supervisor Adapter II family of adapters, and the BladeCenter management module. The user interfaces used to access this hardware are discussed in detail, as is information on how to configure security features such as SSL and authentication features such as LDAP. This book is aimed at customers, IBM Business Partners, and IBM employees who need to understand the capabilities of our systems management hardware, and how to configure and use them to assist with the management of their servers.